2016
DOI: 10.1016/j.jcm.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Hip Strengthening and Manipulative Therapy for the Treatment of Plantar Fasciitis: A Case Report

Abstract: Objective: The purpose of this case report is to describe the management of using a combination of hip strengthening and manipulative therapy (MT) for a patient with plantar fasciitis. Clinical Features: A 44-year-old patient reported heel pain for approximately 1 year before treatment. The patient reported plantar heel pain and tenderness at the calcaneal tuberosity. The pain was most noticeable in the morning but was reduced after a 30-minute walk. A diagnosis of plantar fasciitis was made at the initial ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…A number of studies have also mentioned decreased strength of the core trunk and hip muscles as possible risk factors for PF. 13,14 The reduction in core strength may alter the lower-extremity movement pattern, resulting in excessive femoral adduction and medial rotation as well as knee valgus, all of which may have significant implications for distal limb function. Due to these changes, overload weight-bearing activities produce excessive medial rotation of the femur and tibia as well as more foot pronation, which then leads to disruption of the plantar fascia during the midstance phase of the gait cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have also mentioned decreased strength of the core trunk and hip muscles as possible risk factors for PF. 13,14 The reduction in core strength may alter the lower-extremity movement pattern, resulting in excessive femoral adduction and medial rotation as well as knee valgus, all of which may have significant implications for distal limb function. Due to these changes, overload weight-bearing activities produce excessive medial rotation of the femur and tibia as well as more foot pronation, which then leads to disruption of the plantar fascia during the midstance phase of the gait cycle.…”
Section: Introductionmentioning
confidence: 99%
“…20 An overall review of the literature indicates that physical and psychological factors are reported as the main contributors to pain from PF. 9,11,13,14,16 However, there is a lack of evidence from prospective cohort studies regarding the prognosis of PF. Since pain is the main complaint of patients with PF, the current study was conducted to examine the predictors of pain intensity in individuals with PF.…”
Section: Introductionmentioning
confidence: 99%
“…A recent RCT found that combining HSRT and PFSS protocols with CSI, was significantly more effective than CSI or the combined exercise program alone for pain and function (VAS and FFI) in PHP [41]. Hip strengthening exercise targeting kinetic chain strength deficits not addressed by heel-raise protocols in isolation have also been found to have positive effects for PHP [24,[88][89][90].…”
Section: Discussionmentioning
confidence: 99%
“…There is some limited evidence that a manual therapy approach including ankle joint mobilisation and calf soft tissue release with deep massage and myofascial trigger point release to increase calf flexibility is helpful in improving function and reducing pain in plantar fasciosis patients, at least in the short term (Martin et al, 2014;Santos et al, 2016;Saban et al, 2014). In practice, manual therapy to assist the effects of exercise would be commonplace and, in the authors opinion, appropriate.…”
Section: Manual Therapymentioning
confidence: 99%